2021
DOI: 10.1007/s00127-021-02028-6
|View full text |Cite
|
Sign up to set email alerts
|

ICD-11 posttraumatic stress disorder (PTSD) and complex PTSD (CPTSD) in treatment seeking veterans: risk factors and comorbidity

Abstract: Purpose Emerging evidence suggests that ICD-11 CPTSD is a more common condition than PTSD in treatment seeking samples although no study has explored risk factors and comorbidities of PTSD and CPTSD in veteran populations. In this study, risk factors and comorbidity between veterans meeting criteria for PTSD or CPTSD using the ICD-11 International Trauma Questionnaire (ITQ) were explored. Methods A sample of help-seeking veterans who had been diagnosed with a mental health difficulty (n = 177) was recruited. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 51 publications
9
51
0
Order By: Relevance
“…The purpose of this brief report was to examine associations between ICD-11 PTSD, CPTSD, and MI related to self and others in a sample of treatment-seeking veterans from the United Kingdom. In keeping with Murphy, Karatzias, et al’s (2020; Murphy, Shevlin, et al, 2020) reports, roughly two thirds of this sample possibly met criteria for ICD-11 PTSD or CPTSD. When compared to counterparts with or without PTSD, veterans who satisfied Cloitre et al’s (2018) criteria for CPTSD reported greater MI related to both perpetration- and betrayal-based events.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The purpose of this brief report was to examine associations between ICD-11 PTSD, CPTSD, and MI related to self and others in a sample of treatment-seeking veterans from the United Kingdom. In keeping with Murphy, Karatzias, et al’s (2020; Murphy, Shevlin, et al, 2020) reports, roughly two thirds of this sample possibly met criteria for ICD-11 PTSD or CPTSD. When compared to counterparts with or without PTSD, veterans who satisfied Cloitre et al’s (2018) criteria for CPTSD reported greater MI related to both perpetration- and betrayal-based events.…”
Section: Discussionsupporting
confidence: 72%
“…Participants were recruited from a national charity in the United Kingdom that offers mental health services to veterans (for more details of the larger study, see Murphy, Karatzias, et al, 2020; Murphy, Shevlin, et al, 2020). In addition to serving with the British military, veterans needed to have a clinical diagnosis of a mental health condition and reside in the United Kingdom.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of C-PTSD in police officers with heightened anxiety and depression is consistent with evidence that anxiety and depression are commonly observed in those with C-PTSD [ 7 ]. Moreover, the relationship between fewer hours of sleep and C-PTSD is supported by evidence that poor sleep could be a risk factor for C-PTSD [ 8 ], although poorer sleep may also be a consequence of C-PTSD. However, the risk of PTSD and C-PTSD did not differ by the total frequency of traumatic events experienced personally and at work, inconsistent with evidence that chronic trauma is a significant risk factor for C-PTSD [ 2–4 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may be relevant in police populations where high workload and unsociable working hours are common. Moreover, a cross-sectional study of the UK population established that alcohol abuse doubled the odds of C-PTSD [ 7 ], and in a study of military veterans those with C-PTSD reported poorer sleep quality compared with those with PTSD [ 8 ]. With 5% of police officers reporting increased alcohol consumption following a work trauma [ 9 ], and meta-analyses demonstrating that 51% of police officers have below average sleep [ 10 ], alcohol intake and sleep quality may be crucial risk factors for C-PTSD in police officers.…”
Section: Introductionmentioning
confidence: 99%